A nationwide assessment of community pharmacists' attitudes towards dispensing errors: A cross-sectional study. Issue 5 (October 2022) - Karout, Samar; Khojah, Hani M.J.; Karout, Lina; Itani, Rania
الملخص: أهداف البحث: الاستغناء عن الأخطاء في صرف الأدوية هي أسباب شائعة للضرر الذي يمكن الوقاية منه للمرضى. ومن المثير للاهتمام، أنه لا يعرف سوى القليل جدا عن انتشارها وأنواعها في بيئة الصيدلة المجتمعية في لبنان بسبب عدم وجود نظام إبلاغ فعال. لذلك، هدفت هذه الدراسة إلى استكشاف تصورات صيادلة المجتمع اللبناني عن أنواع هذه الأخطاء في لبنان، والعوامل الكامنة وراء حدوثها، وأسباب عدم الإبلاغ عنها، بالإضافة إلى الممارسات الحالية للحد منها. طرق البحث: تم إجراء مسح مقطعي من خلال استبانة ذاتي ، باستخدام مقياس من 0-4، تم توزيعه على عينة من صيادلة المجتمع في لبنان. النتائج: استجاب نحو 171 صيدلانيا للمسح، أفاد 68٪ منهم أن الأخطاء في صرف الأدوية شائع، ويعتقد 52٪ أنها تتزايد. كانت العوامل المساهمة الرئيسية المبلغ عنها في الأخطاء في صرف الأدوية أنها غير مقروءة والوصفات غير كاملة، وعبء العمل، وتعدد المهام، والانقطاعات، وتشابه أسماء الأدوية، والتعب. علاوة على ذلك، كانت الإستراتيجيات المتصورة للحد من أخطار التدمير الذاتي هي التعاون مع الأطباء، وتحسين الكتابة اليدوية، والفحص المزدوج، وتقديم المشورة المناسبة للمرضى، وتشجيع الإبلاغ، وإصدار المبادئ التوجيهية. أخيرا، كانت الأسباب الرئيسية لنقص الإبلاغ عن الفاعلين تتمثل في عدم وجود التزام بالإبلاغ (59٪) ونقص أنظمة الإبلاغ (56٪). الاستنتاجات: قد تكون الأخطاء في صرف الأدوية سائدة جدا في لبنان لأنها تذهب دون رقابة من قبل السلطات. يوصى بشدة بأنظمة وصف الأدوية الإلكترونية والتقارير العادلة، جنبا إلى جنب مع دراسات المتابعة. Abstract: Objectives: Dispensing errors (DEs) are common causes of preventable harm to patients. Interestingly, very little is known about their prevalence and types in the community pharmacy setting in Lebanon due to the lack of an effective reporting system. Therefore, this study aims to explore the perceptions of community pharmacists about the types of these errors in Lebanon, the factors behind their occurrence, the reasons for underreporting, and the current practices for reducing them. Methods: A cross-sectional survey was conducted through a self-administered questionnaire, using a scale of 0–4, distributed among a sample of community pharmacists in Lebanon. Results: A total of 171 pharmacists responded to the survey, of whom 68% reported that DEs were common, and 52% believed that they were increasing. The main reported contributing factors to DEs were unreadable and incomplete prescriptions (≈3.0 ± 1.0 out of 5), workload, multitasking, interruptions, similarity in names of medications, and fatigue (≈2.5 ± 1.0). Moreover, the perceived strategies to limit the risks of DEs were collaboration with physicians, improving handwriting, double-checking, proper patient counselling, encouraging reporting, and issuance of guidelines (≈3.2 ± 1.0). Finally, the main reasons for underreporting DEs were the lack of obligation to report and the lack of reporting systems (59% and 56%, respectively). Conclusions: DEs may be very prevalent in Lebanon because they are unmonitored by the authorities. Electronic prescription and fair reporting systems are highly recommended, along with follow-up studies.